Significance of financial literacy among women entrepreneurs on Halal business - Fatah Yasin, Raudlotul Firdaus; Mahmud, Mek Wok; Diniyya, Aulia Arifatu (HH Publisher, 2020)
Muslim women have created a unique space for them in the economy by advocating halal entrepreneurship. Islam has encouraged women to engage in business activities. However, Muslim women are struggling to gain acknowledgement from society and face multiple challenges, including limitations in running the business. Besides the gender gap that is prevalent globally, women also have limited knowledge about business. They run the business based on their informal managerial experience and little understanding of financial literacy. This study identifies the characteristics of Muslim women entrepreneurs who engage in entrepreneurship as well as their challenges in running the business.